The influence of brand equity on customer loyalty through customer satisfaction (Study on iPhone users in Bandar Lampung) (Lighthouse Publishing, 2023)
Considering that a number of studies have demonstrated that satisfaction is not always accompanied by loyalty, the company began to shift the paradigm of its business strategy to focus on consumer loyalty as a foundation for understanding how to maintain its brand equity. Despite high levels of consumer satisfaction, businesses are beginning to observe customer loss. This study sought to investigate the impact of brand equity variables on iPhone customer satisfaction and loyalty in Bandar Lampung. The data utilized in this study are primary data obtained from the responses to a questionnaire administered to respondents. There were 130 participants in this study's sample. The sampling procedure employs purposive sampling, a technique for determining the selection based on the researcher-specified criteria. This study employs the Structural Equation Model (SEM) with the Partial Least Square (PLS) technique and the SmartPls 4.0 application for its analysis. According to the findings of this study, perceived quality, perceived cost value, brand identification, brand trust, and lifestyle alignment have a significant impact on consumer satisfaction variables. The customer satisfaction variable has a significant effect on the customer loyalty variable as well.